Antibacterial and Cytotoxicity Effects of Aloe Vera Leaves Extract Gel and Zinc Oxide Nanoparticles (ZnO NPs) on Bacterial Skin Infections - Ahmed Kshash, Noor; S. Ahmed, Ali (Al-Nahrain Journal of Science, 2025)
The skin establishes an immunological barrier against bacterial infections. Despite the presence of several bacterial species on the skin, they typically lack the capacity to infect people. A bacterial skin infection can vary in size from a little area to extensive coverage and in severity from benign to life-threatening. Four identified isolates by VITEK-2 for Staphylococcus spp; S1, S1 Control, S2 and S2 Control were used in this study. S1, S1C, S2 and S2C were collected from alopecia disease assigned by S1, S2 and the healthy hair skin from the same patients (S1C and S2C). The ZnO NPs was green synthesized (GS- ZnO NPs) by aqueous extraction of Aloe vera leaves gel (AG) and characterized by UV-V is spectrometry, Atomic force microscope (AFM), Fourier transform infrared spectroscopy (FTIR), Scanning electron microscope (SEM) and XRD spectroscopy. Minimum inhibitory concentration (MIC) was determined for AG and GS-ZnO NPs, mixture of standard ZnO NPs and AG leaves extract in addition to standard ZnO NPs against Staphylococcus spp. (S1,S1C,S2 and S2C). Cytotoxicity was assessed by MTT assay against normal skin cell, Human dermal fibroblast (HdFn). Compared to the control group, the viability rate was drastically reduced at a dosage of 400 mg/mL. Results showed that the GS-ZnO NPs have the better MIC result (0.400 ±0.03, 0.650 ±0.07, 0.478 ±0.08 b, 0.632 ±0.08) on S1, S1C, S2 and S2C, respectively. The HdFn were slightly more affected by the cytotoxic effects of GS-ZnO NPs, at concentration of 400 mg/mL compared to the control group (100%) (p